SPORT DEVELOPMENT IN THE USA - Mamanazarova Xurshida Sherbek qizi; Botirova Hakima (Лучшие интеллектуальные исследования, 2023)
Annotation: The aim of the article is researching about developing of sport in the USA. In this paper, the history, sport infrastructure and development facilities have been shown.